PENETASAN TELUR IKAN GABUS (Channa striata) DALAM MEDIA INKUBASI DENGAN LAMA PEMBERIAN OKSIGEN (AERASI) BERBEDA - Muslim Muslim; Danang Yonarta (Universitas Teuku Umar, 2017)
The aims of this research were to determine the hatching percentage of snakehead fish egg which incubated on different duration of aeration (oxygen supply). This research had been conducted in the Fish Breeding Unit “Batanghari Sembilan”, Indralaya since October until November 2017. This research used Completely Randomized Design method (CRD) with 5 treatments and 3 replications consist of; P1 (24 hours, aerated), P2 (24 hours non aerated), P3 (12 hours aerated, 12 hours non aerated), P4 (10 hours aerated, 14 hours non aerated) and P5 (8 hours aerated, 16 hours non aerated). The result of this research showed that the best hatching percentage, were P4 81.64%. Survival rate of pro larva (3 day old / D3), the best result were treatment 4 (P4), 86,54%. Baside on, hatching percentage and survival rate of prolarva parameter, P4 is the best treatment. Furthemore, time efficiency and cost of operation fish breeding program, treatment P4 suggested.